Analyse exploratoire des captures de civelles d'anguille (Anguilla anguilla L.) dans l'estuaire de l'Adour - Bru, N.; De Casamajor, M.N.; Dossou-Gbete, Simplice; Truong-Van, B. (HAL CCSD, 1997)
National audience